EFECTO DE LA COPULACIÓN DURANTE EL CELO POSTOVULATORIO EN LA MORTALIDAD EMBRIONARIA EN ALPACAS - Aparicio M., María (2003)
The objetive of this research work was to study the effect of the frequency of copulation during the post-ovulatory estrous on the embryonic mortality in alpacas. Forty four female alpacas were selected having a post-partum sexual rest >20 days and bearing in the ovaries a pre-ovulatory follicle >7 mm of diameter. Animals were mated (time of coitus: >15 minutes) using a male with proven fertility and received 6 g of busereline i.m. after copula to ensure ovulation. Three experimental groups were then ramdomly organized: the first group (S1, n = 14) did not receive additional matings, the second gropup (S2, n = 15) received an additional mating on day three post-ovulation, and the third group (S3, n = 15) received additional matings on days three and four postovulation. Ovulation was confirmed through ultrasound images by disappearance of the pre-ovulatory follicle 42 hours post-mating and the presence of a corpus luteum on day 5 post-ovulation. In addition, the size of the corpus luteum, morfological changes of the uterine horns and presence of an embryo were recorded on days 13-14 and 19 postmating. These observations were complemented with the observation of sexual receptivity using a male on days 6, 13-14, 19 and 26 post-mating. Ovulation rate was 91%. There was a higher tendency on embryo survival at day 19 post-mating in those alpacas that received an additional mating on days 3 (S2 = 80%) and 3 and 4 (S3 = 85%) post-ovulation than in those animals without additional mating (S1 = 75%). An additional study in four inducedovulated alpacas was done to detect fertilized ova at days 2, 3 and 4 post-ovulation. Recovery of the fertilized ova from oviduct was possible only until day 3 post-ovulation.